Effect of Helium Neon Laser Irradiation on Magnesium Levels in Blood "An Experimental Study" - Auhida Ali Abdulsamad, Bassma; Abdel Salam Al sagheer, Fatima (Scientific Journal of University of Benghazi, 2025)
This study investigates the effect of Helium-Neon laser radiation on magnesium levels in blood, a vital element involved in numerous physiological and biochemical processes in the body. The Helium-Neon laser used in this study had a power output of 5 mW and a wavelength of 632.8 nm, known for its stability and low thermal effect. The spot size was approximately 0.03 cm², ensuring uniform exposure of the samples. The energy density delivered to the samples was calculated at 1.0 J/cm², providing an adequate level of irradiation without significant thermal damage. Twenty healthy, non-smoking volunteers aged between 19 and 65 participated in the study. Blood samples were collected in Red Top Tube (RTT) tubes and immediately centrifuged to separate the serum. Centrifugation was performed at 3000 RPM for 3-5 minutes at 25 °C. The separated serum was then divided into four equal portions. The first, the control, had its magnesium level measured using a biochemical analyzer (BS-230), and the mean was 1.84 mg/dL, within the normal range. The remaining three aliquots were exposed to the Helium-Neon laser for 1, 3, and 5 minutes, respectively. Results showed a 60% increase in magnesium in the immediate response, 25% with a decrease, and 15% with no noticeable change. Females showed a greater average magnesium increase (30%) with a more sustained response and greater consistency over time compared to males. Males exhibited more pronounced oscillations, a tendency for initial reductions, and faster returns to baseline. At the 1-minute mark, no significant difference was found between males and females (p > 0.05). However, at 3 and 5 minutes, the difference became statistically significant (p < 0.05), with females showing a higher increase in magnesium levels than males. The precise mechanism underlying these in vitro effects on serum remains unclear. However, it is hypothesized that Helium-Neon laser irradiation might induce subtle conformational changes in serum proteins (e.g., albumin), potentially altering their magnesium-binding affinity and thereby influencing measured levels within the serum milieu. These findings suggest complex, non-thermal interactions between Helium-Neon laser light and serum components in vitro, warranting further research to elucidate the specific biomolecular interactions